The trends of mortality, aetiologies and risk factors of lower respiratory infections in China from 1990 to 2019: Findings from the Global Burden of Disease Study 2019 - Liangyu Kang; Wenzhan Jing; Qiao Liu; Jue Liu; Min Liu (Elsevier, 2022)
Abstracts: Background: Lower respiratory infections (LRIs) are an important public health problem in China. This study aimed to estimate the fatal burden of LRIs in China and trends from 1990 to 2019, thereby making targeted prevention strategies. Methods: Annual deaths and mortality were collected from the GBD 2019. Estimated annual percentage changes (EAPCs) of age-standardized mortality were calculated to quantify the trends of LRI mortality. We also analyzed four aetiologies and 14 risk factors. Results: In China, total deaths due to LRIs decreased from 543,901 (95 %UI 472,378-606,600) in 1990 to 185,264 (95 %UI 160,993-216,219) in 2019. From 1990-2019, the age-standardized mortality decreased by an average of 5.68 % (95 %CI 5.46 %-5.89 %) per year, whereas the reduction among adults older than 70 years (EAPC=−2.56,95 %CI −2.68 to −2.43) was slower than that among children under 5 years (EAPC=−10.11,95 %CI −10.46 to −9.76). Moreover, Streptococcus pneumoniae was the first leading aetiology of LRI mortality among all ages. Although LRI mortality attributable to child undernutrition decreased rapidly from 2000 to 2019, alcohol use (EAPC=−1.06,95 %CI −1.40 to −0.72), smoking (EAPC=−3.70,95 %CI −3.89 to −3.51), and ambient particulate matter pollution (EAPC=−4.00,95 %CI −4.28 to −3.73) remained serious risk factors. Conclusions: LRIs remain an important health problem in China particularly in children under 5 years and adults older than 70 years. Continuous efforts are needed to promote maternal and child health, control smoking and alcohol use, and improve ambient air quality. More researches focusing on LRIs are required to provide targeted and updated prevention strategies.